Evaluation of rheological and image properties of styrene-butadiene-styrene and ethylene-vinyl acetate polymer modified bitumens - Topal, Ali; Yılmaz, Mehmet; Kök, Baha Vural; Kuloğlu, Necati; Şengöz, Burak (My University, 2011)
This article presents a laboratory evaluation of conventional, fundamental, rheological, and morphological characteristics of styrene-butadiene-styrene (SBS) and ethylene vinyl acetate (EVA) polymer modified bitumens. Polymer modified bitumen (PMB) samples have been produced by mixing a 50/70 penetration grade unmodified (base) bitumen with SBS and EVA copolymer at different polymer contents. The fundamental viscoelastic properties of the PMBs were determined using dynamic (oscillatory) mechanical analysis and presented in the form of temperature and frequency-dependent rheological parameters. The morphology of the samples as well as the percent area distribution of polymers throughout the base bitumen have been characterized and determined by means of fluorescent light optic microscopy and Qwin Plus image analysis software, respectively. The results indicated that polymer modification improved the conventional and rheological properties of the base bitumen. It was also concluded that the temperature and frequency had a significant effect on complex modulus of PMBs. The behavior of EVA and SBS PMBs had exhibited quite difference at 50ºC. Moreover, it was found out that at low polymer contents, the samples revealed the existence of dispersed polymer particles in a continuous bitumen phase, whereas at high polymer contents a continuous polymer phase has been observed.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Asphalt; Polymer modification; Rheology; Image analysis